Same same…but different? Support for the ideal of democracy vs. solid democratic support - Moncagatta, Paolo; Saris, Willem E.; Fierro, Mateo (Revista Latinoamericana de Opinión Pública, 2023)
Measurement of citizen support for democracy has been problematic, as most research on the topic has focused on assessing support for an abstract concept: the “ideal” of democracy. This article proposes a different conception of democratic support, labeled “solid democratic support”, which combines multiple items tapping attitudes towards various essential attributes of democratic rule. Using data from the AmericasBarometer surveys, the “solid support” measure is compared to a traditional measure of support for the ideal of democracy in Chile and Venezuela. Important differences are found in the levels of the two indicators and in their correlates, demonstrating that they are in fact different concepts. As well, substantial differences are found between the two countries, suggesting that analyses of democratic support that do not consider the country-specific political context may be flawed.